Contribution of maximal strength to peak power and rate of power development in bench press movement using free weights - Koshida, S.; Iwai, K.; Kagimori, A.; Urabe, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of the study was to demonstrate the relationships between peak power output, rate of power development (RPD) and maximal strength in the bench press movement with free weights. Eighteen healthy male subjects volunteered to participate in the study (mean age 21.1±1.4year, standing height 169.9±6.5cm, body mass (BM) 75.6±16.8kg). All subjects had moderate to extensive resistance training experience ranging from 1 to 5 years. The bench press movement was performed with a weight of 50% of one repetition maximum (1RM). Acceleration data were obtained with a uniaxial micromachined accelerometer attached to the centre of a barbell shaft. Based on the acceleration data, peak power output (W), time to peak power (TPP, s) and RPD (W/s) were computed. Significant correlations were found between peak power per body mass vs. 1RM/BM (r = 0.650, p < 0.01) and RPD/BM vs. 1RM/BM (r = 0.557, p < 0.01). However, RPD/BM and TPP were not significantly different between the high-strength group and the low-strength group. The current findings indicate that increasing maximal strength may play a great role in the peak power improvement, but not on the RPD using free weights. Authors recommend mixed training strategy using a heavy weight and a light to medium weight to effectively improve the bench press performance.